TERAS LIBRARY UNTUK MENINGKATKAN MINAT BACA SISWA SEJAK DINI DI SEKOLAH DASAR - Biya Ebi Praheto; Octavian Muning Sayekti (Universitas Sarjanawiyata Tamansiswa, 2019)
Reading Opening Window The world is a pearl word that describes the importance of reading habits among people. Reading can provide a wealth of knowledge and information from different disciplines in any part of the world. Seeing this, reading has an important role to educate the next generation of the nation. The term reading culture will be a mere discourse if it does not begin with reading habits from an early age. It is the habit that will build the reading culture in Indonesia. According to data from UNESCO in 2012 mentioned that reading interest in Indonesia is only 0.001. That is every 1000 residents only one person who has an interest in reading. The low interest in reading in Indonesia is of particular concern to academics. TerasÂ Library is one of the solutions to instill interest and reading habits in elementary school early on. The habit that is planted early on can be a character that is embedded in students to adulthood. The TerasÂ Library will bring the book closer to the students so that students can read the book casually according to the characteristics of elementary school-age children. With the cultivation of interest and reading habit from an early age, it is expected in the long run there is no longer the term